Understanding the role of specialized mouthparts in the selective feeding of dung beetles (coleoptera: scarabaeinae) - Mathikge, Nthabiseng Gladys (My University, 2021)
The use of a complex food substance such as herbivore dung, by dung beetles has promoted the evolution of an adaptive feeding strategy known as particle feeding. Selection of fine particulate matter elevates the food nutrient quality by up to five-fold. However, it is not known how dung beetles achieve this. An ephemeral food source such as dung is not always available, thus several dung beetle genera have resorted to exploring alternative diets such as dead plant material and mushrooms, dry dung pellets and carrion to name a few. How they use similar mouthparts to process this food is not known. Dung beetles possess highly specialized mouthparts, but how these operate is still not fully understood. Several hypotheses attempting to explain the mode of action of these mouthparts have been put forward but only one has been consistent with several experimental findings. This hypothesis suggests that dung beetles increase the nutrient quality of dung using their mouthparts as a filtering apparatus that concentrates minute and nutritious dung particles while eliminating excess water and intractable plant fragments with no nutritional value. To gain more insight on this topic, this study investigated the morphology of various internal components of dung beetle mouthparts to understand their respective roles in particle feeding. Microscopy and geometric morphometric analysis were used to examine and compare the mouthparts of 12 dung beetle species belonging to four feeding groups (generalist, wet dung, carrion and dry diet feeders). The qualitative microscopy analysis revealed that dry diet feeders possess grinding and cutting structures, which are reduced or absent in the generalist, carrion and wet dung feeders. Dry diet feeders are hypothesized to have evolved from a wet-dung feeding lineage, thus they may have gained cutting and grinding structures as a result of adaptations to environmental changes that confined them to arid habitats. The carrion feeder and generalist feeder have similar structural features as the wet dung feeders, presumably because of a pre-adaption to liquid-based food. The microscopy findings also reveal that the generalist, carrion and wet feeders possess structures such as filtration channels and the prosthecal comb that are heavily reduced in dry feeders. Based on comparisons made between the dry feeder Pachysoma striatum which shares morphological similarities with all of the feeding groups, it was concluded that the likely function of the filtration channels is to facilitate the movement of ready to digest food from the molar lobes to the pharynx to be ingested. The quantitative microscopy results indicate that the filtration channels are not designed to effectively expel excess water, thus Holter’s hypothesis is not entirely valid and needs to be revised. The mouthpart dimensions measured in my thesis in relation to the particle size range determined by Holter and Scholtz (2007) and Madzivhe et al. (2020) show that the mouthparts do not function as a filter in the strictest sense as proposed by Holter (2000) and I have thus proposed a rake – like mechanism. The geometric morphometrics results indicate that distinct structural features of dung beetle mouthparts across feeding groups are determined by taxonomic relationships shared between species rather than food habits. Thus, the use of the shape of the epipharynx for geometric morphometrics is more useful for understanding phylogenetic relationships between species than it is for mapping feeding behavioural differences across feeding groups.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science, 2021